PENGARUH EKSTRAK BROTOWALI ( Tinospora crispa L.) TERHADAP PENAMPILAN REPRODUKSI MENCIT (Mus musculus L. Swiss Webster) BETINA - Sari, Fitri Malinda; Widiana, Rina; Sumarmin, Ramadhan (STKIP PGRI Sumbar, 2014)
ABSTRACT Tinospora crispa (brotowali) is known as a dill in Indonesia. Brotowali have bioactive compounds which useful for medicine. It can found at all part of this plant. Tinospora crispa stem has bitter kolumbin, alcaloid and glicoside. Alcaloid is antiproliferative. This antiproliferative can reduce the amount of oosit which is produced and decrease the amount of oosit which is ovulated so it affects the reproduction performance of mice. This research has purpose to know the effect of Tinospora crispa extract to the reproduction performance of mice. This research is experimantal research used female mice (Mus musculus L.) as many as 24 female mice which are divided into 4 treatments and 6 replication. The treatments given is brotowali extract with variety of dosages, they are: K is control, P1 treatment (5x10-2), P2 (6x10-2) and P3 (7x10-2) gram/mice. The parameterobserved is the amount of corpus Luteum, implantations, resorptions, died fetus and alive fetus. The data is parametric which is measured by Analisis of Varians then by DNMRT. The result shows that brotowali extract to the female mice with 0 day till 16th day pregnance has significantly higher (p<0,05) to the amount of corpus Luteum, the alive fetus, the died fetus and resorption. While, the amount of implantation has not significantly. Thus, it can be concluded that brotowali extract for the female mice pregnant have embryotoxic and fetotoxic effects.